Some Legal Controversies Regarding Party-affiliated Endowments and Their Participation in Business Activities: The Case of EFFORT and TIRET Endowments - Messelu, Mamenie; Markides, Professor Costas (Bahir Dar University Journal of Law, 2023)
Social service needs in no way can be fulfilled by the government alone.That is why governments are giving due consideration for Civil SocietyOrganizations (hereinafter CSOs) and incorporating them in their legalframeworks. Charitable endowment is among the different classificationsof CSOs, which play a significant role in every walk of life as they fill thegaps that the government fails or is unable to discharge its responsibilityin various dimensions including human rights protection and socioeconomic development. In Ethiopia, party affiliated endowments such asEndowment Fund for the Rehabilitation of Tigray (EFFORT), AmharaNational Regional State Rehabilitation and Development Fund (TIRET),Endowment Foundation for the Development of Oromia (TUMSA), andEndowment Fund for the Development of Southern Nation Nationalitiesand Peoples (WENDO) are established by Tigray Peoples LiberationFront (TPLF), Amhara National Democratic Movement (ANDM),Oromia Peoples Democratic Organization (OPDO), and Southern NationNationalities and Peoples Democratic Movement (SEPDM) respectively,on the assumption that the wider public of each regional state communityis the beneficiary of these endowments. This article examined the legalityof formation, registration, and operation of these endowments and theirparticipation in business by using EFFORT and TIRET endowments as acase study. The article upholds doctrinal legal research which is basedon the identification, synthesis and analysis of the law definingendowment and their participation in business. The finding shows thatthere is defective formation of EFFORT and TIRET endowments, andalso that their involvement in business activities is contrary to theprovisions of the laws regarding commerce, tax, competition, and CSOs.